2020
DOI: 10.1371/journal.pone.0242079
|View full text |Cite
|
Sign up to set email alerts
|

Total replacement of fishmeal with poultry by-product meal affected the growth, muscle quality, histological structure, antioxidant capacity and immune response of juvenile barramundi, Lates calcarifer

Abstract: The present study investigates if the total replacement of dietary fishmeal (FM) with poultry by-product meal (PBM), supplemented with methionine influences the muscle fatty acids composition, normal gut morphology, histological traits of the liver, muscle, and gill, liver enzymes, immune and antioxidant response, and stress-related gene in juvenile barramundi, Lates calcarifer in relation to growth and feed utilization. Barramundi (3.58±0.01g) were randomly distributed into six 300 L seawater recirculating ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
39
2
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 86 publications
6
39
2
3
Order By: Relevance
“…The total substitution of FM with PBM concomitantly supplemented with TH and HI larvae improved the growth and condition factor in barramundi. Our earlier 20 and other study by Siddik, et al 21 evaluating the total FM substitution with PBM resulted in poor growth performance in barramundi . Also, many other studies reported negative outcomes in the growth of a number of fish when dietary inclusion of PBM exceeded > 50% [15][16][17] .…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…The total substitution of FM with PBM concomitantly supplemented with TH and HI larvae improved the growth and condition factor in barramundi. Our earlier 20 and other study by Siddik, et al 21 evaluating the total FM substitution with PBM resulted in poor growth performance in barramundi . Also, many other studies reported negative outcomes in the growth of a number of fish when dietary inclusion of PBM exceeded > 50% [15][16][17] .…”
Section: Discussionmentioning
confidence: 66%
“…Histological damages of immune-sensitive organs including liver, kidney, and spleen could be easily assessed when host species are fed non-FM diets. For example, total substitution of FM with PBM resulted in lipid droplets and multifocal necrosis in the liver of barramundi 13 , 20 . Similarly, higher replacement of FM with PBM (50–70%) and animal protein blend containing PBM, shrimp meal and spray-dried blood meal (20–80%) induced hepatocytes steatosis in juvenile hybrid grouper, Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂ 8 , 93 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, very little is known about the effects of land animal proteins as fishmeal replacements on the liver and intestinal histology. Findings from the limited studies that have been reported up to date have revealed that high inclusion levels of land animal proteins may induce hepatic steatosis and increase hepatic lipid vacuolization in Lateolabrax japonicus [19], in hybrid grouper [20,21] and in Lates calcarifer [22]. In addition, negative effects on the intestinal histology have also been reported with the fishmeal replacement by land animal proteins [22,23].…”
Section: Introductionmentioning
confidence: 99%